Analysis of the SAMR Model and Psychological Approach on Duolingo Livestreams by Hololive VTubers in Learning Japanese - Mohammad, Wily; Maulidiyah, Nabilla Ryca (Jurnal Pendidikan Non formal, 2023)
This qualitative research endeavors to investigate the innovative intersection of technology, persona, and psychology in language education through a unique lens—the world of VTuber Hololive Duolingo livestreams. The study's primary objective is to analyze the transformative potential of this approach to language learning, guided by the SAMR (Substitution, Augmentation, Modification, Redefinition) model and psychological perspectives. Employing purposive sampling, the research centers around six Hololive VTubers: Ceres Fauna, Ouro Kronii, Nanashi Mumei, Gawr Gura, Ninomae Ina'nis, and Moona Hoshinova. The investigation uncovers how these VTubers, each with distinct personas, employ the Duolingo application to teach Japanese on livestreams and its impact on viewers' language acquisition. The findings illuminate the multifaceted effects of technology integration, ranging from familiarity to transformative language learning experiences using SAMR, accompanied by psychological engagement and motivation. This study contributes to the evolving landscape of language education in the digital age and offers a foundation for future research in this captivating domain.